Large format backside illuminated CCD imager for space surveillance. - Tower, J.R.
The key features and performance data of a 2560×1960-pixel split-frame-transfer imager developed for space surveillance is described. The eight-port, backside illuminated charge coupled device (CCD) features 24 μm pixels with buried blooming drains to provide 100% optical fill-factor and >1000× overload protection from blooming. The imaging and storage registers are strapped with metal to achieve vertical transfer clock rates >400 KHz for the 61 mm long imaging register gates. The 5 million pixel array operates at 2.7 frames/s. The monolithic focal plane includes a 32×32-pixel frame-transfer imager, with a single output, which operates at 1000 frames/s. The output ports employ a floating diffusion output circuit with responsivity of 10.5 μV/e and noise of 7e RMS at a 1.25 MHz clock rate. The imager is photocomposed employing a combination of 5× and 1× lithography. The photocomposition approach is described.
Keywords: 1960 pixel; 24 micron; 2560 pixel; 5017600 pixel; Buried blooming drains; Eight-port backside illuminated charge coupled device; Floating diffusion amplifier; Floating diffusion output circuit; Ground-based deep space surveillance; Imaging registers; Large format backside illuminated CCD imager; Lithography; Metal strapping; Monolithic focal plane; Noise; Optical fill-factor.; Overload protection; Photocomposed imager; Photocomposition approach; Responsivity; Space surveillance; Split-frame-transfer imager; Storage registers; Vertical transfer clock rates